Hubungan Status Gizi, Umur, dan Jenis Kelamin dengan Derajat Pneumonia pada Balita di RSUP Dr. M. Djamil Padang Periode Januari 2018 – Desember 2018 - Faris Saadi Firdaus; Eva Chundrayetti; Siti Nurhajjah (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Pneumonia is an acute infection of lower respiratory tract. Pneumonia in under 5-year-old children is a health problem in developing countries, including Indonesia. Nutritional status, age, and sex are risk factors that increase the severity of pneumonia. Objective.The study aims to determine the relationship of nutritional status, age, and sex to severity of pneumonia in under 5-year-old children at Dr. M. Djamil General Hospital Padang in the period from January to December 2018. Methods.The study is of analytical cross-sectional design.The data is collected from the hospitals’s medical records department. The sample is 57 under 5-year-old children diagnosed with pneumonia at Dr. M. Djamil General Hospital Padang in the period from January to December 2018. Simple random sampling is used to select the sample. Chi-square tests are applied in data analysis. Results.The highest incidence of pneumonia is found in the category of severe pneumonia (64,9%), the age group of 2-24 months (73,7%), among males (52,6%), and nutritional status of normal and overnutrition (64,9%). The results of the chi-square test used to determine the relationship of nutritional status, age, and sex to severity of pneumonia are respectively p = 0,015, p = 0,033 and p = 0,532. Conclusion.There are relationships of nutritional status and age to severity of pneumonia, but no relationship of sex to severity of pneumonia